2000
DOI: 10.1002/1521-3862(200008)6:4<193::aid-cvde193>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

MOCVD of Thin Ruthenium Oxide Films: Properties and Growth Kinetics

Abstract: Conducting thin films of RuO 2 were grown on glass by metal±organic chemical vapor deposition (MOCVD) at substrate temperatures down to 623 K. Tris-trifluoroacetylacetonate-rutheniumIII (Ru(tfa) 3 ) served as the precursor. Film properties, such as resistivity, were improved by the addition of water to the reaction gas. The films were investigated by X-ray diffraction (XRD) and four-probe resistivity measurements. The growth mechanism was studied by in situ ellipsometry, and a model reaction mechanism is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Previously, in situ spectroscopic ellipsometry (SE) was used to study growth of thin RuO 2 films during thermal oxidation of Ru. 24,25 However, it should be noted that extracting information from SE involves reconstruction of both optical constants and layered structure, a process which is often uniquely determined. We used in situ hard x-ray reflectivity measurements for monitoring thermal oxidation of Ru thin films.…”
mentioning
confidence: 99%
“…Previously, in situ spectroscopic ellipsometry (SE) was used to study growth of thin RuO 2 films during thermal oxidation of Ru. 24,25 However, it should be noted that extracting information from SE involves reconstruction of both optical constants and layered structure, a process which is often uniquely determined. We used in situ hard x-ray reflectivity measurements for monitoring thermal oxidation of Ru thin films.…”
mentioning
confidence: 99%
“…However recently a large number of ruthenium complexes like ruthenium alkoxides, ruthenium alkyls, ruthenium amidinates, ruthenium diketonates, ruthenium carbonyls and others were exploited as precursor complexes. 1,53,[81][82][83][84] Thus, it is interesting to classify such complexes in terms of the nature of bonding of organic ligands formed by ruthenium and is described as follows: 2 were exploited as CVD precursors. 87 The molecular structures of some important ruthenium carbonyls are depicted in Fig.…”
Section: Different Classes Of Ruthenium Complexes Used As Cvd Precursorsmentioning
confidence: 99%
“…A mixture of oxygen and water as carrier gas improved several thin lm properties like resistivity. The thin lm growth mechanism was studied by in situ ellipsometry 53 which showed that the nucleation occurred with lateral and vertical island growth in a rst step followed by a homogeneous lm growth preserving the surface roughness. A model reaction mechanism is proposed for growth kinetics: The reaction kinetics follows a rst-order Langmuir-Hinshelwood mechanism with growth rate dependent deposition parameters.…”
Section: Different Classes Of Ruthenium Complexes Used As Cvd Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, spectroscopic ellipsometry (SE) can be used for in situ monitoring thin film growth. 283,284 However, it should be noted that extracting information from SE involves reconstruction of both optical constants and layered structure, a process which is often non-uniquely determined. (Specular) X-ray reflectivity (XRR) is another example of technique that can be used for in situ monitoring thin film growth.…”
Section: X-ray Reflectivity 2351 Motivation For Its Usementioning
confidence: 99%